Use of heat-pressed, leucite-reinforced ceramic on anterior and posterior onlays: A clinical report - (:unkn) unknown (MOSBY, INC, 2002)
The introduction of new techniques and materials in all-cera-mic systems, together with improvements in resin bonding agents, has enabled the use of resin cements to directly bond ceramic crowns, veneers, and inlays/onlays to conservative tooth preparations. Directly bonded ceramic onlays can eliminate the need for conventional means of retention and allow the restoration of lost tooth structure with minimal tooth preparation. This article presents the use and short-term clinical performance of directly bonded, heat-pressed, leucite-reinforced ceramic onlays in both anterior and posterior areas of the mouth.
Keywords: DENTAL RESTORATIONS; SURVIVAL; SYSTEMS; INLAYS